Between Past and Future - 1/5
Recording of the international conference "Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" organized by CEU and the University of Maryland, held at CEU between 26th and 28th of March, 1999. After giving the presentations, the members of the media panel “1989 and its Aftermath through the Eyes of the Media” launch into a debate about the legacy of communism and media perception. The speakers are R. W. Apple Jr. (Chief Correspondent, “New York Times”), Barrie Dunsmore (Former Senior Correspondent, ABC News), James Carney (Political Correspondent, “Time Magazine”), Flora Lewis (Senior Columnist, “New York Times” Syndicate), Ambassador Richard Holbrooke (U.S. Special Envoy to Yugoslavia), György Bolgár (Journalist and Broadcaster, Hungarian Radio) and Kati Marton, the Chairman of the conference panel.